Den stulna myten: Samtida speglingar av antiken - Jackson, Peter (Nordlit, 2014)
The Stolen Myth: Contemporary Reflections of Antiquity. Proceeding from Roland Barthes’ debunking of ”Romans on film” in the now classical collection Mythologies from 1956, this paper attempts to scrutinize certain popular notions about Greek Antiquity as resulting from so-called hypercorrections of the past. A recent exhibition of reconstructed polychrome statues and reliefs from Classical Antiquity (White Lies), and the Hollywood blockbuster movie Troy, are seen as indicative of this hypercorrecting urge. The arguments goes that such versions of the past – while still being symptomatic of an emergent historical consciousness – suffer from a lacking appreciation of the categories ‘myth’ and ‘history’ in their pre-modern relationship of dynamic complementarity.